Krill availability in adjacent Adélie and gentoo penguin foraging regions near Palmer Station, Antarctica - Nardelli, Schuyler C.; Cimino, Megan A.; Conroy, John A.; Fraser, William R.; Steinberg, Deborah K.; Schofield, Oscar (W&M ScholarWorks, 2021)
The Palmer Deep canyon along the West Antarctic Peninsula is a biological hotspot with abundant phytoplankton and krill supporting Adélie and gentoo penguin rookeries at the canyon head. Nearshore studies have focused on physical mechanisms driving primary production and penguin foraging, but less is known about finer-scale krill distribution and density. We designed two acoustic survey grids paired with conductivity–temperature–depth profiles within adjacent Adélie and gentoo penguin foraging regions near Palmer Station, Ant-arctica. The grids were sampled from January to March 2019 to assess variability in krill availability and associations with oceanographic properties. Krill density was similar in the two regions, but krill swarms were longer and larger in the gentoo foraging region, which was also less stratified and had lower chlorophyll concentrations. In the inshore zone near penguin colonies, depth-integrated krill density increased from summer to autumn (January–March) independent of chlorophyll concentration, suggesting a life history-driven adult krill migration rather than a resource-driven biomass increase. The daytime depth of krill biomass deepened through the summer and became decoupled from the chlorophyll maximum in March as diel vertical migration magnitude likely increased. Penguins near Palmer Station did not appear to be limited by krill availability during our study, and regional differences in krill depth match the foraging behaviors of the two penguin species. Understanding fine-scale physical forcing and ecological interactions in coastal Antarctic hotspots is critical for predicting how environmental change will impact these ecosystems.